A narrative review of turning deficits in people with Parkinson's disease. (July 2015) - Hulbert, Sophia; Ashburn, Ann; Robert, Lisa; Verheyden, Geert
Abstract Purpose: Clinically, people with Parkinson's disease (PD) demonstrate a loss of axial rotation of the spine often described as moving "enbloc", with little dissociation between the head, trunk and lower limbs whilst turning. The purpose of this narrative review is to explore the behaviour and relationship of the reported deficits during whole body turning in people with PD, compared to controls. Better understanding of the relationship and impact of the deficits will permit the development of tailored and novel intervention strategies to improve functional performance in turning for people with PD. Methods: Four electronic databases with the search terms: Parkinson* and turn* were used. Results: Seventy-seven papers were reviewed. Turning deficits in people with PD were identified as originating from two hypothetical body segments – perpendicular (i.e. legs) or axial (i.e. head, trunk and pelvis) segments and the relationship between them discussed. Conclusion: Specific movement deficits in turning in people with PD can be categorised into axial and perpendicular deficits. Synthesis of the literature suggests the possibility of axial deficits driving secondary responses in the perpendicular segments. This should be explored when designing rehabilitation aimed at improving turning performance, as current therapy guidelines focus on exercises emphasising perpendicular aspects. Implications for Rehabilitation Turning performance is compromised in people with PD, which can lead to significant disability, falls and loss of function. Specific movement deficits can be categorised into perpendicular deficits (taking more steps and shorter steps and an altered turn strategy) and axial deficits (segment rigidity, altered segment co-ordination and timing, reduced segment rotation and the effects of altered posture). Axial deficits may drive secondary responses in the perpendicular segments during turning in people with PD. Therefore, specific focus should be made to the rehabilitation of the axial deficits alongside those of the perpendicular body segments in the design of multi-modal treatment strategies to improve turning performance.